Social Seed Networks for Climate Change Adaptation in Western Kenya: Results from a study to better understand farmers’ primary sources of seed information in the Nyando Climate-Smart Villages - Otieno, Gloria Atieno; Lacasse, Hannah; Fadda, Carlo; Reynolds, Travis W.; Recha, John W.M. (2018)
Kenyan smallholder farmers are vulnerable to the effects of climate change, including increased temperatures and variability in precipitation, which results in shorter growing seasons in most areas of East Africa (Adhikari et al. 2015). One strategy for adapting to these climactic changes is to utilise genetic resources to mitigate the effects of abiotic and biotic stresses (IPCC 2014). Farmers could benefit from accessing and exchanging genetic resources, seed, and the information needed to use those resources effectively. Farmers’ seed networks are believed to supply about 80% of seed to farmers in Kenya, where, for example, 75-80% of seed used by farmers’ is from ‘informal’ systems. Farmer seed networks are important for accessing seed and providing genetic diversity that is vital for resilience (Louwaars et al., 2013). Research in East Africa has suggested that community-generated information sharing might support more effective farmer response to the changing seasonal and weather patterns associated with climate change (Comes et al. 2015). However, little is known about the farmers’ social seed networks in supporting adaptation to climate change in Kenya.